VARIABILITY OF QUANTITATIVE PROPERTIES IN OILSEED RAPE - Brassıca napus L., AND EFFICIENCY FROM APPLICATION OF CERTAIN MACRO AND MICROELEMENTS - Iljovski, Igor, Dimov Zoran, Kabranova Romina, Arsov Zlatko, Canev Ile, Tanaskovic Vjekoslav, Dimovska Daniela (Trakya University Publisher, 2019)
Determination of quantitative characteristics by using macro and microelements that have great importance on the development of oilseed rape - Brassica napus L. started by setting the experiment (2014), and applying Mg and Mn as elements corresponding for the purpose. The trials were set in order to see the impact of magnesium and manganese on the quantitative properties of winter oilseed rape genotypes - Brassica napus L.. For this purpose, certain concentrations of magnesium sulphate and manganese chelate by foliar fertilizer application was applied on 3 genotype winter oilseed rape (Hybrirock, Petrol and Speed) in 5 variants, as follows: Variant 1 Control Ø NPK, Variant 2 NPK+MgSO4 25%, Variant 3 NPK+MgSO4 35%, Variant 4 NPK+Mn chelate 20%, and Variant 5 NPK+Mn chelate 30%. By specifying the appropriate fertilizers with Mg and Mn (their concentrations), except for quantitative properties, the adaptability of the tested genotypes of specific agro-climatic and soil conditions was observed and the following parameters were monitored: plant height (cm), the number of branches/plant, number of pods/plant, pod length (cm), the number of seeds in the pod and seed yield (t/ha). According to the results of the preliminary experiment can be concluded that higher concentrations of magnesium sulphate (35%) and manganese chelate (30%) leads to increased the components of yield and seed in tested genotypes. Efficiency of variants, generated by certain concentrations of fertilizers has also confirmed impact of higher concentrations; in terms of dosages and prices of yields (NPK+Mn chelate 30% and NPK+Mg SO4 35%).
Keywords: oilseed rape, magnesium, manganese, yield, efficiency, DEA